International diversiﬁcation and risk in investment portfolio - Chura Palacios, Luz (2020)
To demonstrate the eﬀect of International Diversiﬁcation on the risk of Investment Portfolio and has as secondary objectives: obtaining an eﬃcient frontier for the analysis and comparison of investment options in various international markets. The present work is a type of non-experimental, quantitative cross-sectional, descriptive and explanatory research that is based on the quantiﬁcation of indicators of ﬁnancial assets listed on the Stock Exchange of Chile, Brazil, the United States, Switzerland, Spain, Hungary, India and Japan in the period between 2011-2019 for the formation of investment portfolios. For the purposes of the present research, 40 shares listed on the Stock Exchange of Chile, Brazil, the United States, Switzerland, Spain, Hungary, India and Japan were taken as reference universe. However, after a debugging process based on the levels of correlation between assets, there were 24 actions, organized into 3 assets per market, for the development of the present investigation. Subsequently, the proﬁtability and variance was obtained by applying portfolio optimization analysis and in this way the eight eﬃcient borders for the eight international markets were obtained. In the formation of investment portfolios, the theory of international diversiﬁcation was applied, for which the levels of adjusted proﬁtability were compared with the risk of portfolios. The results obtained allowed us to identify that diversiﬁcation between countries represents a signiﬁcant alternative to maximize proﬁtability. In addition, it represents a signiﬁcant alternative for reducing the risk of investment portfolios. Through a country approach, diversiﬁcation alternatives exist due to the low level of correlation.